Optical mapping of Tip-Enhanced Raman Spectroscopy (TERS) - Mishuk, Md. Nasimuzzaman (BARC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2017.